Code of Ethics and the Role of Advocates in Providing Legal Aid to the Poor - Nuna, Muten; Kodai, Dince Aisa; Moonti, Roy Marthen (Indonesian Journal of Advocacy and Legal Services, 2020)
Law No. 18 of 2003 concerning Advocates emphasizes the status of Advocates as one of the law enforcers who have roles and functions that are equal to the Police, Prosecutor's Office and Judicial Power as law enforcement officers, but there is specialness given by the law to lawyers, namely the independence of advocates in carrying out their duties and profession. The independence of advocates aims to support the implementation of a justice system that is free from power and political intervention in law enforcement, and with that independence the Advocate Profession is said to be a very noble profession (offiicium nobile). As a noble profession, of course, advocates are bound by ethical values ​​that become the guidelines in the implementation of their duties and authorities, where those values ​​are posited as a Professional Code of Ethics. Talking about advocates, of course it cannot be separated from law enforcement, talking about law certainly cannot be separated from the state system or the political colors of certain countries and so on. This article wants to explain how the code of ethics of the advocate profession in upholding the law is how the role of advocates in providing justice to society based on applicable law. In conclusion, this article wants to explain that the code of ethics can compensate for the negative aspects of the profession and with the existence of a code of ethics, community trust in a profession can be strengthened, because every client has the assurance that his interests will be guaranteed, and the implementation of legal aid must be in line with the breath that becomes the goal is protection human rights and ideals of justice.